Behavioural research on human working memory: mixing qualitative and quantitative methods - Bacigalupe, María de los Ángeles (2013)
The long lasting opposition between qualitative and quantitative methods for studying behaviour has been overridden by interdisciplinary work in which methods can be combined to approach animal and human behaviour, thus contributing to drawing rigorous and useful conclusions. We show an example of this by combining a quasi-experimental design and descriptive methods to study working memory for the resolution of a spatial problem task (the Tower of Hanoi) in a neuropsychiatric hospital inpatient with amnesia and executive deficits. Results from the quasi-experiment showed that the patient acquired strategies to solve the task with a high level of efficiency (F3/35 = 7, 19, p < .01). Qualitatively speaking, the patient developed more than one strategy to solve the problem, which indicates the presence of learning based on working memory. In the light of these findings, we discuss issues of mixed methods research and suggest the importance of developing mixed methods to study behaviour.